The attractiveness of local food sourcing for retailers in Portugal - Sousa, Maria Isabel Melo e (2021)
This work project analyses the overall attractiveness of local food sourcing for retailers in Portugal and how this is affected by their size or strategy. Open-ended surveys to various retailers showed that this corporate social responsibility practice is a business priority and guarantees freshness and quality when goods come directly from producers. Consumer surveys demonstrated a preference for national products. However, uncompetitive prices and scarcity area significant setback to both retailers and consumers. Ultimately, local sourcing's attractiveness is not identical for every business as they do not possess the same resources and capabilities to exploit its potential.